Curriculum, assessment, and accreditation in teacher education programs. An analysis of National Plans in Argentina (Itinerarios Educativos, 2021)
Since the creation of the National Institute for Teacher Education in Argentina, teacher education policies are revealed in three national plans developed in different national government administrations. Each one generated a set of regulations that aimed at adjusting these policies to each provincial context. This diversity of stages, contexts, and definitions leads to the need for an analysis of plans continuity, undergone changes, and the dynamics of the implementation  of the defined policies. This work is part of a research project of Universidad Pedagógica Nacional of Argentina and its object of analysis is preschool teacher education through the comparative study of curricular policies, accreditation, and comprehensive assessment. These measures demand a constant compromise between the national state and Argentine jurisdictions, since any change introduced into national guidelines affects every provincial institution. This article provides an analysis of the federal concertation processes, the role played by the national state, and the tensions between federal, provincial, and institutional scopes as regards preschool teacher education.
Keywords: teacher education; curricular policies; of teacher education assessment